Circular RNA-based biomarkers in blood of patients with Fabry disease and related phenotypes. Issue 3 (5th February 2021) - Nowak, Albina; Haddad, George; Kistler, Andreas D; Nlandu-Khodo, Stellor; Beuschlein, Felix; Wüthrich, Rudolf P; Lorenzen, Johan M; Kölling, Malte
Abstract : Background: Fabry disease is a rare X-linked lysosomal storage disease caused by mutations in the galactosidase α gene. Deficient activity of α-galactosidase A leads to glycosphingolipid accumulations in multiple organs. Circular RNAs represent strong regulators of gene expression. Their circular structure ensures high stability in blood. We hypothesised that blood-based circular RNA profiles improve phenotypic assignment and therapeutic monitoring of Fabry disease. Methods: A genome-wide circular RNA expression analysis was performed in blood of genetically diagnosed patients with Fabry disease (n=58), age-matched and sex-matched healthy volunteers (n=14) and disease control patients with acute kidney injury (n=109). Most highly dysregulated circular RNAs were validated by quantitative real-time PCR. Circular RNA biomarker sensitivity, specificity, predictive values and area under the curve (AUC) were determined. Linear regression analyses were conducted for validated circular RNA biomarkers and clinical patient characteristics. Results: A distinct circular RNA transcriptome signature identified patients with Fabry disease. Level of circular RNAs hsa_circ_0006853 (AUC=0.73), hsa_circ_0083766 (AUC=0.8) and hsa_circ_0002397 (AUC=0.8) distinguished patients with Fabry disease from both healthy controls and patients with acute kidney injury. Hsa_circ_0002397 was, furthermore, female-specifically expressed. Circular RNA level were significantly related to galactosidase α gene mutations, early symptoms, phenotypes, disease severities, specific therapies and long-term complications of Fabry disease. Conclusion: The discovery of circular RNA-based and Fabry disease–specific biomarkers may advance future diagnosis of Fabry disease and help to distinguish related phenotypes.